Bacterial-driven upcycling spent Ag into high-performance catalyst for toxic organics reduction. (October 2022) - Li, Xiaohong; Li, Shunling; Gan, Kai; Bai, Xiongfei; Li, Shuli; Tang, Congkui; Li, Lei; Qu, Qing
Abstract: Achieving up-cycling and reusing of silver from the waste X-rays films is currently a huge challenge. Here, we designed a facile method that upcycles Ag + extract efficiently from waste film into highly dispersed value-added biological Ag/AgO–AgCl nanoparticles (bio-Ag/AgO–AgCl NPs) using Bacillus thuringiensis -secreted extracellular polymeric substance without additional reductants and electron donors. The recovery efficiency of silver exceeded 99.8%. Surprisingly, the bio-Ag/AgO–AgCl NPs can well solve the bottleneck problem of slow Ag catalytic kinetics. When the amount of catalyst was 1.9 mg, the reduction efficiency and reduction rate of 10 ppm methyl orange were 97.9% and 7 min, and that of 30 ppm Congo red were 95.3% and 5 min respectively, which is superior to other chemically synthesized silver-base catalysts. This bioremediation methodology provides an effective and practical technical approach for precious metal remediation and sustainable energy development. Graphical abstract: Image 1 Highlights: A way to converse waste Ag to value-added bio-Ag/AgO–AgCl NPs by EPS was proposed. The recovery efficiency of bio-Ag/AgO–AgCl NPs exceeded 99.8%. Bio-Ag/AgO–AgCl NPs showed excellent catalytic activity for typical toxic organics. The abundant adsorption sites on the nanoparticles were responsible for high catalytic activity.